The Effect of Saliva Zink Levels with Nutrition Status of Elementary School Children in Air Beliti Puskesmas Year 2021 - Aini, Putri Citra Qurrothu; Flora, Rostika; Zulkarnain, M.; Ocktariana, Ocktariana; Tanjung, Risnawati (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The impaired nutrition in children is a very important problem because it has a direct impact on the growth and development of children. Malnutrition in children can lead to micronutrient deficiencies including zinc. Zinc is an important mineral found in every cell and is needed to support the body's immune system, heal wounds, help the ability to taste and smell and is needed in the DNA synthesis process. The purpose of this study was to examine the relationship between salivary zinc with the nutritional status of elementary school children in the Air Beliti Public Health Center work area. Methods: This study is an observational study with a cross-sectional design. The study was conducted on 76 respondents who met the inclusion criteria. Measurement of Height for Age to determine the nutritional status of children and examination of salivary zinc levels with the ELISA method to determine salivary zinc levels. The data was analyzed using the Spearman correlation test. Results: The results of the measurement of nutritional status showed that 46.1% of children were stunted and 53.9% of children had normal nutritional status. The results of the measurement of salivary zinc levels showed that the average salivary zinc level in stunted children was 1.96 mmol/L, while in children who were not stunted, it was 2.43 mmol/L. Salivary zinc levels in stunted children were lower than in children who were not stunted. Conclusions and Suggestions: There is an effect of saliva zinc examination on the nutritional status of schoolchildren. It is necessary to increase the intake of nutrients, especially zinc, in children so that their nutritional status is not disturbed. Also, check the nutritional status of children by adding variables that can describe the nutritional status of children in accordance with their development and growth.Â